Simultaneous Local Election in Indonesia: Is It Really More Effective and Efficient? - Nugroho, Rahmat Muhajir; Asmorojati, Anom Wahyu (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Election system that is not carried out simultaneously, among others, has led to high political costs of local election. One of the objectives of the simultaneous local election design is the budget efficiency of the election implementation. This study aims to evaluate whether the simultaneous local election implementation may create a more effective and efficient local elections in the Special Region of Yogyakarta and South Kalimantan. This research was conducted using a normative juridical approach by analysing the applicable legal regulations, particularly Law Number 8 of 2015. In addition, an empirical juridical approach was used to see the implications of the establishment of Law Number 8 of 2015 on the Local Election. The results of study showed that the simultaneous local elections held in the Special Region of Yogyakarta and South Kalimantan were more effective and efficient in terms of controlling and solving problems, budgeting and time used for the implementation of the local election.